2021
DOI: 10.1590/1678-5150-pvb-6749
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of actions of the official veterinary service to mitigate outbreaks of infectious laryngotracheitis and improve biosecurity on laying hen farms

Abstract: Infectious laryngotracheitis (ILT), caused by an Alphaherpesvirus (Gallid herpesvirus-1; GaHV-1), has been noticed in the region of the Terras Altas da Mantiqueira, Minas Gerais. From 2010 to 2018, the “Serviço Veterinário Oficial” (SVO) of the “Instituto Mineiro Agropecuário” (IMA), implemented measures to prevent spread of the virus to other regions and control the disease in the area. Due to the close proximity and consequent epidemiological link among farms, the region was considered a unique epidemiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The biosecurity measures implemented at the start of the outbreak (Hergot et al 2021) varied among the farms, as did the immunization protocols using either HVT or FPV based ILTV recombinant vaccines. Chickens were initially vaccinated in 2011 and sampled for diagnostic purposes thereafter (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The biosecurity measures implemented at the start of the outbreak (Hergot et al 2021) varied among the farms, as did the immunization protocols using either HVT or FPV based ILTV recombinant vaccines. Chickens were initially vaccinated in 2011 and sampled for diagnostic purposes thereafter (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…When health/veterinary services fail, the occurrence of endemic disease and the risk of disease entry from a border are likely to increase (Lubroth et al, 2017). Hergot et al (2021) studied the actions of the official veterinary service (OVS) to mitigate outbreaks of infectious laryngotracheitis (ITL -GaHV-1) and improve biosecurity on laying hen farms in the Minas Gerais State (Brazil) and observed that the actions of the OVS were fundamental to preventing the spread of the virus to other regions. The main actions were: vaccination of chickens quarantined on the farms; manure treatment and controlled transportation of manure, chickens and other waste from farms; sanitary education programmes; farms outside the quarantined area were kept infection free for eight years (2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018); restrictive measures to improve biosecurity and monitoring of ILT cases.…”
Section: Introductionmentioning
confidence: 99%